Attempt to set the reference value for the clinical stabilometry with a sampling frequency of 100Hz - Ueda, Naoko; Asai, Masatsugu; Shojaku, Hideo (Equilibrium Research, 2021)
In order to set a draft reference value for clinical stabilometry by 100Hz sampling, we collected and reported the data of 365 healthy subjects. The subjects were divided into 7 ten-year age groups, from the 20s to the 70s, and a group of over 80. As a draft reference value, we thought that it might be reasonable to use the mean ±2×standard deviation and the 95th percentile/5th percentile together. In this analysis, mixed gender data were used, as, based on the results of statistical analysis, we considered that the reference value could be used as a standard value for both men and women.